2001
DOI: 10.1111/1467-8489.00148
|View full text |Cite
|
Sign up to set email alerts
|

Changes in regional inequality in rural China: decomposing the Gini index by income sources

Abstract: A new method is proposed to decompose inequality changes as measured by the Gini index 1 into structural e¡ects, real inequality e¡ects and interactive e¡ects. Application of the method to updated Chinese data reveals that structural e¡ects represent the driving force underlying the increasing trend in regional income inequality in rural China. Policy implications are explored. In addition to these contributions, considerable e¡orts are made to construct the income data used in the article. Pitfalls in measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…The majority of empirical studies reported in Table 1 do not adjust for spatial price differences, although such differences exist and may substantially change the results for both developing countries such as China (see Wan 2001) and free market economies such as the US (see Ram 1992). Price levels are often correlated with living standards, so adjusting for spatial price differences will tend to lower the between-group term in the spatial decomposition while…”
Section: Observation 6: Spatial Price Variationsmentioning
confidence: 99%
“…The majority of empirical studies reported in Table 1 do not adjust for spatial price differences, although such differences exist and may substantially change the results for both developing countries such as China (see Wan 2001) and free market economies such as the US (see Ram 1992). Price levels are often correlated with living standards, so adjusting for spatial price differences will tend to lower the between-group term in the spatial decomposition while…”
Section: Observation 6: Spatial Price Variationsmentioning
confidence: 99%
“…On the other hand, education was the second largest contributor and its position more or less matched that of industrialization since 1996. The contribution of industrialization is large but smaller than that suggested by earlier studies of Rozelle (1994) and Wan (2001). Such an inconsistency is most likely due to contamination in early analytical frameworks, where other factors were not controlled for.…”
Section: Sources Of Rural Regional Inequalitymentioning
confidence: 61%
“…Such an inconsistency is most likely due to contamination in early analytical frameworks, where other factors were not controlled for. Wan (2004) obtained a smaller contribution than Rozelle (1994) and Wan (2001) after controlling for some variables. However, Wan (2004) did not incorporate regional dummy variables in his income function.…”
Section: Sources Of Rural Regional Inequalitymentioning
confidence: 78%
See 2 more Smart Citations